Factors affecting the overwintering of tadpoles in a temperate amphibian. (18th October 2015) - Walsh, P. T.; Downie, J. R.; Monaghan, P.
Abstract: Temperate anuran amphibians generally complete metamorphosis by the autumn of their natal year, but there are an increasing number of reports of overwintering of the larval tadpole phase. We currently know little about the environmental cues that trigger this change in the temporal pattern of development, or if it has any fitness consequences. In an experimental study in the laboratory, we examined the effects of environmental temperature and food availability on the temporal pattern of larval development and the proportion of individuals that overwintered as larvae, in Rana temporaria from the UK. The proportion of overwintering tadpoles increased with lower temperature and food availability. No overwintering tadpoles appeared to arrest their larval development early in the season, contrary to expectations from field observations. Therefore, other factors beyond mean temperature and food availability may be involved in the overwintering phenomenon observed in the field. Furthermore, all overwintering tadpoles were large enough to commence metamorphosis in the autumn, but this was delayed until spring, and on completion of metamorphosis overwintered tadpoles were larger than individuals that had completed metamorphosis within their first summer. While developmental and growth constraints certainly play a role in overwintering as larvae in the laboratory, the larger size on completion of metamorphosis may represent an adaptive advantage for this phenomenon. The extent to which the larger size of overwintering tadpoles is advantageous would presumably vary with local conditions and individual survival prospects.